Ultrafast Carrier-Coupled Interlayer Contraction, Coherent Intralayer Motions, and Phonon Thermalization Dynamics of Black Phosphorus - Chebl, Mazhar; He, Xing; Yang, Ding-Shyue (Nano letters, 2022)
Black phosphorus (bP) exhibits highly anisotropic properties and dynamical behavior that are unique even among two-dimensional and van der Waals (vdW) layered materials. Here, we show that an interlayer lattice contraction and concerted, symmetric intralayer vibrations occur concurrently within few picoseconds following the photoinjection and relaxation of carriers, using ultrafast electron diffraction in the reflection geometry to probe the out-of-plane motions. A strong coupling between the photocarriers and bP’s puckered structure, with the alignment of the electronic band structure, is at work for such directional atomic motions without a photoinduced phase transition. Three temporal regimes can be identified for the phonon thermalization dynamics where a quasi-equilibrium without anisotropy is reached in about 50 ps, followed by propagation of coherent acoustic phonons and heat diffusion into the bulk. The early time out-of-plane dynamics reported here have important implications for single- and few-layer bP and other vdW materials with strong electronic–lattice correlations.